Cell Signaling, Inflammation & Disease - Joseph, Mitchelle; Joseph, Mitchelle; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Cell Signaling, Inflammation and Disease is a multidisciplinary, open access journal which offers a specialized home for research within the field of cell signaling as it applies to specific topics such as chronic disease, inflammation, sepsis. Cell Signaling, Inflammation and Disease is a sister title to Cell Communication and Signaling.
Keywords: Cytology; Cytology; Diseases; Proteins; 9; Cytokines; Cell Biology; Mechanisms of Disease; Proteins; Protein Biochemistry; Cytokines and Growth Factors